EFFECT OF RECOGNITION AND INVOLVEMENT IN DECISION-MAKING ON THE MENTAL WELL-BEING OF FEMALE SECONDARY SCHOOL TEACHERS IN LAGOS STATE (Journal of the Management Sciences, 2024)
This study investigated the effects of recognition and involvement in decision-making on the mental well-being of female secondary school teachers in Lagos State, Nigeria. Using the descriptive survey research design, the study sampled 459 respondents using purposive sampling from a population of 6,271 female teachers. Two hypotheses were stated and tested using Structural Equation Modeling (SEM). The results revealed a significant effect of recognition on mental well-being (β = .162, p < .05), and a significant effect of involvement in decision-making onthe mental well-being of female teachers (β = .217, p < .05). These findings suggest that both recognition and participative decision-making significantly enhance the mental well-being of female teachers. Consequently, it is recommended that educational authorities implement systematic recognition programs and encourage inclusive decision-making processes to improve teachers’ mental health. These measures are particularly crucial for female teachers who face unique challenges related to gender roles and societal expectations.
Keywords: recognition, Involvement in decision-making, mental well-being, and teachers